THE EFFECT OF SOMATIC AUDITORY VISUAL INTELLECTUAL (SAVI) TECHNIQUE UPON THE READING COMPREHENSION ACHIEVEMENT OF EIGHT GRADE STUDENTS OF SMP NEGERI 3 SINGARAJA IN ACADEMIC YEAR 2015/2016 - YUNIARI, NI MADE (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2015)
AbstractThis study aimed at investigating whether or not there was any significant effect of SAVI technique upon the reading comprehension achievement of the eighth grade students of SMP Negeri 3 Singaraja. On the basis of the purpose of the study, there was a null hypothesis formulated. The sampling technique used in this study was cluster random sampling. Two classes: VIII.C3 and VIII.C5 were selected as the samples of study. Class VIII.C3 was selected as the experimental group and VIII.C5 was selected as the control group. Each class consists of 41 students. In this study, the data were obtained by conducting reading comprehension test: normality and homogeneity test, try-out test, and posttest. The obtain data were analyzed through descriptive and inferential statistics. From the descriptive analysis, it was found out that the mean score for the group using SAVI technique was 7.78 while the group using Conventional Reading technique was 7.18. It means that SAVI technique was better than Conventional Reading technique.Â The result of inferential statistic shows that to (2.13) more than tcv (1.98). The null hypothesis which states there is significant effect of studentsâ?? reading comprehension achievement between the two groups was rejected.Â Keywords: Effect, Somatic Auditory Visual Intellectual (SAVI) Technique, Reading ComprehensionÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â AbstrakPenelitian ini bertujuan untuk menyelidiki apakah ada pengaruh yang signifikan dari teknik SAVI terhadap pencapaian dari pemahaman membaca siswa kelas delapan SMP Negeri 3 Singaraja. Berdasarkan tujuan penelitian tersebut, ada hipotesis null yang diformulasikan. Teknik sample yang digunakan pada penelitian ini adalah Cluster Random Sampling. Ada dua kelas yang dipilih sebagai sampel yakni kelas VIII.C3 dan VIII.C5. Kelas VIII.C3 dipilih sebagai grup eksperimen sedangkan VIII.C5 dipilih sebagai grup control. Tiap kelas terdiri dari 41 orang siswa. Pada penelitian ini, data yang didapat dianalisa melalui descriptive dan inferential statistics. Dari analisis deskriptif ditemukan bahwa skor mean untuk grup yang menggunakan teknik SAVI adalah 7.78, sedangkan grup yang menggunakan teknik Reading konvensional adalah 7.18. ini berarti teknik SAVI lebih baik daripada teknik Reading konvensional. Hasil dari inferential statistic menunjukkan bahwa to (2.13) lebih dari tcv (1.98). hipotesis null yang menyatakan bahwa ada pengaruh yang signifikan dari pencapaian dari pemahaman membaca siswa antara dua grup ditolak.Â Kata Kunci: Pengaruh, Teknik Somatic Auditory Visual Intellectual (SAVI), Pemahaman MembacaÂ